The effect of payroll taxes on employment and wages under high labor informality - Arturo Antón (IZA Journal of Labor & Development, 2014)
This paper evaluates the effects of a fall in payroll taxes on employment and wages in the presence of high labor informality. For that purpose, the paper examines a recently approved tax reform in Colombia especially targeted to promote labor formality. The model suggests that the reform would increase total employment by between 0.3 to 0.5 percent and formal employment by between 3.4 to 3.7 percent over the pre-reform scenario. In addition, formal wage rates would increase by 4.9 percent as a result of the reform. This finding suggests that the pass-through effect in labor markets may be large in these economies.
Keywords: E62; H26; J21; O17; 330; Labor informality; Payroll taxes; Tax incidence